Preschool-aged children recognize ambivalence: emerging identification of concurrent conflicting desires - Rostad, Kristin; Pexman, Penny M. (Frontiers in Psychology, 2015)
We examined the ability of preschool-aged children to identify conflicting, or ambivalent, desire states (e.g., “I want to go to the birthday party because there will be cake, but I also don’t want to go because I’m having fun playing at home”). Participants were 4- and 5-year-old children, and a group of undergraduate students (n = 20 in each age group). They were presented with 14 scenarios involving both ‘single desire’ and ‘dual desire’ states, including both approach (i.e., ‘want’) and avoidance (i.e., ‘not want’) desires. Our primary interest was children’s ability to identify concurrent conflicting ‘dual desire’ states, and this ability was found in most of the 5-year-old age group tested and in about half of the 4-year-old age group. As such, these results provide evidence that children can identify ambivalence at earlier ages than previously reported. In addition, results showed that the challenge in recognizing ambivalence is the presence of desires of opposite valence directed at the same target.